(untitled) (European Journal of Pure and Applied Mathematics, 2012)
By making use of the principle of differential subordination, we investigate several inclusion relationships and other interesting properties of certain subclasses of meromorphically multivalent functions which are defiÂ…ned by certain linear operator involving the generalized hypergeometric function.